Generalization of Jensen Mercer inequality on Delta integral with Applications (European Journal of Pure and Applied Mathematics, 2023)
The aim of this article is to give generalization of Jensen Mercer inequality on deltaintegral along with applications to Ky Fan inequality and related results.
Keywords: Jensen mercer inequality; Time Scale Calculus; Ky Fan Inequality